1999
DOI: 10.1046/j.1365-3156.1999.43379.x
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Wuchereria bancrofti antigenaemia in Sri Lanka

Abstract: SummaryThe prevalence of Wuchereria bancrofti antigenaemia determined in 353 subjects in Matara, Sri Lanka by Og4C3 ELISA was 20.7%. Positive rates obtained with the same subjects by 1 ml Nuclepore filtration and 60 µl thick blood smear were 11.3% and 7.9%, respectively. Antigen levels were positively associated with microfilaria counts. Two-thirds of antigen-positive and microfilaria-negative (Agϩ/Mf-) individuals were Ͼ 25-year-old, but younger age groups (Յ 25-year-old) tended to have proportionally more Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Our results contradict these observations and clearly show that there is a significant association (p = 0.001) between the density of MF and the concentration of CFA. Similar results were obtained by Rocha et al (1996), Nicolas et al (1997) and Itoh et al (1999). We also agree with Grove and Davis (1978), who suggest that the detection of microfilarial antibodies depends upon the relative release of MF into the bloodstream and the production of antibodies against those MF.…”
Section: Discussionsupporting
confidence: 92%
“…Our results contradict these observations and clearly show that there is a significant association (p = 0.001) between the density of MF and the concentration of CFA. Similar results were obtained by Rocha et al (1996), Nicolas et al (1997) and Itoh et al (1999). We also agree with Grove and Davis (1978), who suggest that the detection of microfilarial antibodies depends upon the relative release of MF into the bloodstream and the production of antibodies against those MF.…”
Section: Discussionsupporting
confidence: 92%
“…In the older group (10-15 years), although the prevalence estimated by the antigen tests was again higher than that estimated by the parasitological methods, this difference was less pronounced. These results demonstrate the lower sensitivity of the parasitological methods in the younger age groups compared with the older population, as a larger proportion of individuals in the prepatent stages or who have amicrofilaremic infections (with adult worms but with no or few reproducing females) are usually found in this population, as previously described 7,33 .…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have shown that the sensitivity of both parasitological and antigen tests decreases as the MF loads decrease 21,31,33,41 . This decrease may result in differential performance across population subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (including this article), do not agree with this hypothesis (Rocha et al 1996, Nicolas et al 1997, Itoh et al 1999). These authors demonstrated on the contrary that the CFA intensity is directly proportional to the microfilaremia density, i.e., the higher the MF density, the higher the CFA levels.…”
Section: Study Population and Parasitological Profile -mentioning
confidence: 71%